Centrifugal–Centripetal Dynamics in the Dialogical Self: A Case Study of a Boundary Experience in Teacher Education. Issue 2 (26th April 2022) - Henry, Alastair; Mollstedt, Maria
Abstract: The dialogical self is conceptualized as a dynamically shifting collection of relatively autonomous I -positions. A boundary experience is an event or situation where tension experienced between conflicting I-positions leads to reconfiguration within the dialogical self. In a boundary experience, uncertainty or a challenge can trigger decentering (centrifugal) movements which can disrupt the self's contingent stability. These movements can be counterbalanced by centering (centripetal) movements aimed at restoring continuity and consistency. Investigating a boundary experience as a process in motion, this individual case study explores centrifugal–centripetal dynamics in the dialogical self of a preservice teacher during a challenging school placement. Data used in the study derives from reflective/reflexive writing in the form of daily contributions to an online discussion between the participant and a dialogue partner. Findings point to the presence of two alternately complementary/conflicting I-positions in the participant's teacher identity system and shed light on the roles played by meta- and promoter positions in addressing identity tensions. Recognizing how a boundary experience can be distributed across a range of events, each of which can contribute to processes of reconfiguration, the study underscores the importance of investigating transformative experiences in contexts of professional learning.